Role of phonic gestures in communication education in kindergarten age children (Selected issues from the theory and practice of speech therapy, 2018)
Phonic gestures are a communication tool and a regulator of social relationships, and their meaning depends on the intention of the sender, which is understood in a particular consituation. In speech therapy every subject performs them: a speech therapist, a parent/carer, a patient. The performed research proved that phonic gestures of various kinds are employed very effectively by kindergarten children. Owing to sonic mimic movements, they build their dialogues, shape and perfect communication skills, very effectively communicate with their environment, express themselves in the course of various communication processes based on a word and/or non-standard verbal elements. Learning to consciously apply signs that act audibly is an important part of (self)reflection of a speech therapist who prepares a little patient for the full and active participation in linguistic interaction.